Pengaruh kombinasi terapi akupunktur dan herbal kelor (moringa oliefera) terhadap penurunan nilai ambang nyeri pada kasus ischialgia di rsu Ja’far medika karanganyar - Jafar Maruf, Ibnu (Jurnal Kesehatan, 2024)
Ischialgia is pain that radiates along the course of the sciatic nerve and its two branches, namely the common peroneal nerve & tibial nerve. This research is quantitative research, using an experimental research design, simple randomized the pretest-posttest control group design (RCT). The sampling technique used in this study was using simple random sampling technique. Research entitled "The Effect of Combination Therapy of Acupuncture and Herbal Moringa (Moringa oliefera) on Reducing Pain Threshold in Ischialgia Cases  at the Ja'far Medika Karanganyar General Hospital". Performed on 44 research subjects who have entered the inclusion and exclusion criteria. A total of 44 people were divided into two groups: group I (intervention) received acupuncture therapy and herbal capsules of Moringa leaf extract (Moringa oliefera) and group II (control), received acupuncture therapy and placebo capsules/empty capsules with each group consisting of of 22 research subjects. From statistical calculations, the following results were obtained: the pain scale of research subjects in group I (intervention) before acupuncture action obtained an average value of 8.36, the value after acupuncture therapy and consumption of herbal capsules of Moringa leaf extract (Moringa oliefera) pain scale 0 ,86. The pain scale of the study subjects in group II (control) before the acupuncture intervention was carried out obtained an average value of 8.36 and the value after acupuncture therapy and consumption of placebo capsules / empty capsules pain scale was 2.55. Statistical test results with the Mann Whitney test obtained a significant value. p = 0.000, if p <0.05 then Ho is rejected and Ha is accepted so that it can be interpreted that Acupuncture Therapy and Herbal Capsules of Moringa Leaf Extract (Moringa oliefera) have an effect on decreasing the pain scale. The conclusion of this study was that there was a significant difference in pain scores using the Visual Analogoque Scale (VAS) between the intervention group who received acupuncture therapy and herbal capsules of Moringa leaf extract (Moringa oliefera) compared to the control group who received acupuncture therapy and placebo capsules/empty capsules. where the intervention group got a lower average VAS pain score than the control group.